2019
DOI: 10.3368/jhr.56.3.1118-9883r1
|View full text |Cite
|
Sign up to set email alerts
|

The Labor Market Consequences of Receiving Disability Benefits during Childhood

Abstract: This paper estimates the labor market effects of gaining eligibility for Supplemental Security Income (SSI) disability benefits during childhood. In theory, access to SSI could help children treat their disabilities, thus improving labor market outcomes in the long run. Alternatively, children who are designated as disabled may reduce their investment in human capital, which would harm future labor market outcomes. I identify the effects of qualifying for SSI benefits through a natural experiment-a Supreme Cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…7 In related work, researchers have shown that receiving SSI as a child influences labor supply outcomes later in adulthood. Deshpande (2016b) finds that removal of a child from SSI at age 18 significantly reduces own future income and increases income volatility, and Levere (2017) 6 labor market and economic outcomes, it is not yet known whether SSI for low birth weight infants affects child development or other family outcomes during early childhood.…”
Section: B Supplemental Security Income For Childrenmentioning
confidence: 99%
“…7 In related work, researchers have shown that receiving SSI as a child influences labor supply outcomes later in adulthood. Deshpande (2016b) finds that removal of a child from SSI at age 18 significantly reduces own future income and increases income volatility, and Levere (2017) 6 labor market and economic outcomes, it is not yet known whether SSI for low birth weight infants affects child development or other family outcomes during early childhood.…”
Section: B Supplemental Security Income For Childrenmentioning
confidence: 99%
“…Although some young adults might seek SSI primarily for the Medicaid coverage, SSI awards also provide cash payments that can add up to substantial expenditures for the federal government, particularly for young adults (Riley & Rupp, 2015). SSI receipt may also discourage work and weaken beneficiaries' human capital over the long term (Levere, 2019). Providing additional stand‐alone options for health insurance to young adults might better meet their need for help in managing the costs of a disabling condition, while increasing their self‐sufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…However, disability benefits programs also have work disincentives, as beneficiaries with sufficiently high earnings eventually lose eligibility. The receipt of benefits, and even the application process itself, can reduce earnings and employment (Maestas et al., 2013; Gelber et al., 2017; Autor et al, 2015; Levere, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since lower birth weight infants should, all else equal, have more delayed motor skills than infants with higher birth weights, these results are especially consequential. Levere (2015) takes advantage of a second source of quasi-experimental variation in SSI coverage, in this case occasioned by the 1990 Sullivan v. Zebley Supreme Court decision, which broadened SSI coverage for children with mental disabilities. Children with mental health conditions who were younger when Zebley was handed down became eligible for more years of SSI support than older children.…”
Section: Supplemental Security Incomementioning
confidence: 99%